Game-based Learning in Science Education: Bibliometric Analysis - Surya Haryandi; Misbah Misbah; Rossy Arlinda; Muhdi Harto; Nurlaela Muhammad; Qamariah Qamariah (CV FOUNDAE, 2025)
Game-based Learning (GBL) in science education can increase students' interest, motivation, and involvement in the process of learning, so a more in-depth study of GBL through bibliometric analysis is needed. This study aims to analyze research trends on the application GBL in science education through bibliometric analysis from 2021-2024. This study employed bibliometric analysis to examine 349 English-language journal articles published from 2021 to 2024, which were retrieved from the Scopus database. Using VOSviewer, the analysis involved co-occurrence and keyword mapping to identify emerging research themes and publication trends. The results obtained 62 articles for further analysis through bibliometric review and visualization using VOSviewer. The trend of GBL research grows yearly, potentially increasing the number of publications the following year. The majority of GBL-related articles appear in respected international journals. This is also the reason for the article's high citation count. Indonesia ranks second in terms of GBL research. The visualization findings between GBL and science education demonstrate that various keywords under investigation emerged in the previous year. This further indicates a topic worth investigating further. The analysis results are based on the study topic, research location, type of research, and applications utilized in GBL, providing an overview for future researchers to undertake a more in-depth examination of the data. The main findings show that GBL may enhance the learning results of students in the context of science, providing insights into effective learning strategies that educators can adopt. These findings are expected to be used to formulate more innovative and effective educational practices and serve as a basis for further research in this area.